Role of membrane undulations in cell adhesion. - Teo, Hui Min. (2009)
Human Red Blood Cells (RBC) undergo several physicochemical changes, in the course of their life span of approximately 120 days. The increased aggregation of senescent RBC continues to be of great interest to clinicians and scientists. Hence, this project aimed to give more insight into the topic, through the observation of RBC treated with varying concentrations the enzyme Neuraminidase, to mimic RBC ageing to differing extents. Through the use of a suitable imaging modality, the Interference Reflection Microscope (IRM), RBC were for quantified with respect to their undulation amplitudes and adhesion energies